2017
DOI: 10.1038/nrneurol.2017.128
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of exercise and physical therapy in people with Parkinson disease

Abstract: Parkinson disease (PD) is a progressive, neurodegenerative movement disorder with symptoms reflecting various impairments and functional limitations, such as postural instability, gait disturbance, immobility and falls. In addition to pharmacological and surgical management of PD, exercise and physical therapy interventions are also being actively researched. This Review provides an overview of the effects of PD on physical activity - including muscle weakness, reduced aerobic capacity, gait impairment, balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
298
1
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(347 citation statements)
references
References 158 publications
7
298
1
13
Order By: Relevance
“…Proposed mechanisms demonstrated in preclinical models include anti-inflammatory, antioxidant, promitochondrial, trophic, and anti-synuclein effects, and small studies in PD patients have shown increased cortical motor excitability, elevated striatal dopamine D2 receptor binding, increased serum levels of brainderived neurotrophic factor, and improvements in gray matter volumes (for a review, see ref. 68 ). Whether these findings truly represent central neuroplastic changes that will have a long-term impact on the natural history of the neurodegenerative process or simply central consequences of improved fitness and physical training will only be established when reliable biomarkers for the disease status become available.…”
Section: Other Treatment Categoriesmentioning
confidence: 99%
“…Proposed mechanisms demonstrated in preclinical models include anti-inflammatory, antioxidant, promitochondrial, trophic, and anti-synuclein effects, and small studies in PD patients have shown increased cortical motor excitability, elevated striatal dopamine D2 receptor binding, increased serum levels of brainderived neurotrophic factor, and improvements in gray matter volumes (for a review, see ref. 68 ). Whether these findings truly represent central neuroplastic changes that will have a long-term impact on the natural history of the neurodegenerative process or simply central consequences of improved fitness and physical training will only be established when reliable biomarkers for the disease status become available.…”
Section: Other Treatment Categoriesmentioning
confidence: 99%
“…[9][10][11] Given the long prodromal stage of PD development, reverse causality cannot be excluded. Finally, the biological mechanisms underlying exercise and a lower PD risk are largely speculative, but may involve increased neuroplasticity and brain-derived neurotrophic factors 12 and a reduction in neuroinflammation. 10,13 Moderate coffee consumption (3-5 cups/day) is associated with lower risk of multiple CV outcomes.…”
Section: Factors That Have Concordant Associationsmentioning
confidence: 99%
“…Additionally, impaired gait negatively affects a person's social participation, which can further reduce quality of life (Hammarlund, Andersson, Andersson, Nilsson, & Hagell, 2014). Gait training is therefore an integral approach within PD rehabilitation, and there is strong evidence that improvements in walking can be maintained up to 6 months after training has ceased (Mak, Wong‐Yu, Shen, & Chung, 2017). Assessment of walking is not only an essential marker of rehabilitation effectiveness, but can also potentially identify those at risk for physical inactivity or falls who require targeted preventive efforts (Canning, Paul, & Nieuwboer, 2014).…”
Section: Introductionmentioning
confidence: 99%